Pengaruh penambahan serat sabut kelapa terhadap kuat tekan dan daya serap air batu cetak beton (bataton) - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Psikologi Universitas Gadjah Mada, 1998)
ABSTRACT A series of test on fibre reinforced concrete bricks was conducted to study the compressive strength and water absorption capacity to improve the quality. The fibres were made of coconut fibres in the length of 60 mm (aspect ratio of 300) and added into the mortar mixes in the proportion of 0.00